Effects of magnesium sulfate on heart rate, blood pressure variability and baroreflex sensitivity in preeclamptic rats treated with L-NAME. (November 2013) - Zhou, Qiongjie; Shen, Jie; Zhou, Guangxing; Shen, Linlin; Zhou, Shufeng; Li, Xiaotian
<x xml:space="preserve">Abstract</x> Objective: Magnesium sulfate is used for the treatment of preeclampsia. This study aimed to evaluate effects of magnesium sulfate on heart rate variability (HRV), blood pressure variability (BPV) and baroreflex sensitivity (BRS) in pregnant rats treated with NG-nitro-.-arginine-methyl ester (L-NAME). Methods: Sprague–Dawley rats were randomly divided into four groups: non-pregnancy and three pregnant groups. From gestational day 2–12, normal pregnancy group (NOR) received sterile water through intravenous injection, LN was injected with L-NAME [25 mg/day] to induce preeclampsia, while LNM group was also treated with magnesium sulfate at 0.3 g/kg at gestational day 13. HRV, BPV and BRS were monitored, and endothelial functions were detected at gestational day 14. Results: Rats with treatment of L-NAME showed significantly increased blood pressure and endothelin-1 concentration and decreased plasma NO concentration; concomitant treatment with magnesium sulfate suppressed blood pressure. Also, rats treated with L-NAME and magnesium sulfate underwent lower heart rate variability (lower absolute and normalized LF) and higher blood pressure variability (lower normalized HF and LF, higher normalized VLF) compared with non-pregnant or normal pregnant rats, whereas normalized LF of HRV in rats co-administered magnesium sulfate returned to normal level. Additionally, rats treated with L-NAME underwent decreased BRS-SP, BRS-NE, BRS LF and HF, and rats with concomitant magnesium sulfate partially reversed the decline (p > 0.05) and had significantly lower BRS-SP, BRS-NE. Conclusion: Sympathetic and parasympathetic impairment exist in preeclamptic rats treated with L-NAME. Magnesium sulfate may ameliorate alterations in the autonomic nervous system noted in preeclampsia.